Magnetic signatures of ion cyclotron waves during Cassini's high-inclination orbits of Saturn. (February 2017) - Meeks, Zachary; Simon, Sven
Abstract: Based on magnetic field data from Cassini's high-inclination orbits of Saturn (radius R S = 60, 268 km ), we analyze the latitudinal distribution of ion cyclotron waves in the giant planet's magnetosphere. Our survey takes into account magnetic field data from all high-inclination orbits between 2004 and 2015. We analyze the dependency of the occurrence rate and amplitude of the ion cyclotron waves on radial distance ρ to Saturn's rotation axis, vertical distance z to Saturn's equatorial plane, and magnetic latitude λ . The occurrence rate of ion cyclotron waves is approximately 100% in Saturn's equatorial plane between the orbits of Enceladus and Dione and decreases to 50% at altitudes of | z | ≈ 0.6 R S . Ion cyclotron waves were detected up to | z | = 2.0 R S . The occurrence rate displays strong, non-monotonic variations with respect to ρ, z, and λ . The vertical amplitude profile of the waves exhibits an M-like pattern with two distinct peaks near z = ± 0.3 R S and the central minimum at z =0. Compared to earlier observations, we find this M-like structure to be inflated in± z direction by a factor of three. The available magnetic field data provides only weak evidence for a local impact of Enceladus and Dione on the ion cyclotron wave field. Using the observed Doppler shift of the ion cyclotron wave frequency during Cassini's high-inclination orbits, we demonstrate the existence of a narrow band of bidirectional wave propagation. This band is centered around Saturn's equatorial plane and possesses a half-width of | z | = 0.15 R S, which agrees well with the vertical scale height of Saturn's neutral cloud. To the north of this band, all ion cyclotron waves propagate towards the north ( z > 0 ); and to the south, all waves propagate towards the south ( z < 0 ). In companion with our previous study (Meeks et al., 2016), this survey provides the complete three-dimensional picture of the ion cyclotron wave field between the orbits of Enceladus and Rhea during the Cassini era. Abstract : Highlights: Vertical ion cyclotron wave occurrence rate profile. Vertical ion cyclotron wave amplitude profile. Extent of ion cyclotron wave generation region. Propagation of ion cyclotron waves. Effect of Enceladus, Dione, and Rhea on ion cyclotron wave field.